Synthesis of trifunctional cyclo-β-tripeptide templates - Stein, Frank; Mehmood, Tahir; Plass, Tilman; Zaidi, Javid H.; Diederichsen, Ulf (Beilstein Journal of Organic Chemistry, 2012)
The concept of template-assembled synthetic proteins (TASP) describes a central scaffold that predefines the three dimensional structure for diverse molecules linked to this platform. Cyclic β-tripeptides are interesting candidates for use as templates due to their conformationally defined structure, stability to enzymatic degradation, and ability to form intermolecular stacked tubular structures. To validate the applicability of cyclic β-tripeptides within the TASP concept, an efficient synthesis of the cyclopeptide with orthogonal functionalization of the side chains is desired. A solid-phase-supported route with on-resin cyclization is described, employing the aryl hydrazide linker cleavable by oxidation. An orthogonal protection-group strategy allows functionalization of the central cyclic β-tripeptide with up to three different peptide fragments or fluorescent labels.
Keywords: β-amino acids; cyclic β-tripeptide scaffold; orthogonal protection groups; peptide synthesis; template-assembled synthetic proteins (TASP)